Feasibility Studies for Quarkonium Production at a Fixed-Target Experiment Using the LHC Proton and Lead Beams (AFTER@LHC). (4th October 2015) - Massacrier, L.; Trzeciak, B.; Fleuret, F.; Hadjidakis, C.; Kikola, D.; Lansberg, J. P.; Shao, H.-S.
Abstract : Being used in the fixed-target mode, the multi-TeV LHC proton and lead beams allow for studies of heavy-flavour hadroproduction with unprecedented precision at backward rapidities, far negative Feynman-x, using conventional detection techniques. At the nominal LHC energies, quarkonia can be studied in detail in p + p, p + d, and p + A collisions at s N N ≃ 115  GeV and in Pb + p and Pb + A collisions at s N N ≃ 72  GeV with luminosities roughly equivalent to that of the collider mode that is up to 20 fb −1  yr −1 in p + p and p + d collisions, up to 0.6 fb −1  yr −1 in p + A collisions, and up to 10 nb −1  yr −1 in Pb + A collisions. In this paper, we assess the feasibility of such studies by performing fast simulations using the performance of a LHCb-like detector.